PENGARUH 4P GREEN MARKETING MIX TERHADAP KEPUASAN PELANGGAN BLOOMKA SKINCARE - Mila Dwi Astuti (2021)
This study aims to analyze and prove whether there is an effect of green product, green orice, green place and green promotion on customer satisfaction. This research method is quantitative with a sample of 100 bloomka customer respondents who are domiciled in the DKI Jakarta area. The data analysis technique used is descriptive analysis and inferential analysis with Smart PLS 3.0 analysis tool. The results of this study indicate that the green product variable has an effect on customer satisfaction of 0.369. Green price has an effect on customer satisfaction of 0.286. Green place has an effect on customer satisfaction of 0.208. Green promotion has no effect on customer satisfaction.